Involvement of lipid transfer proteins in resistance against a non‐host powdery mildew in Arabidopsis thaliana. (11th October 2018) - Fahlberg, Per; Buhot, Nathalie; Johansson, Oskar N.; Andersson, Mats X.
SUMMARY : Non‐specific lipid transfer proteins (LTPs) are involved in the transport of lipophilic compounds to the cuticular surface in epidermal cells and in the defence against pathogens. The role of glycophosphatidylinositol (GPI)‐anchored LTPs (LTPGs) in resistance against non‐host mildews in Arabidopsis thaliana was investigated using reverse genetics. Loss of either LTPG1, LTPG2, LTPG5 or LTPG6 increased the susceptibility to penetration of the epidermal cell wall by Blumeria graminis f. sp. hordei ( Bgh ). However, no impact on pre‐penetration defence against another non‐host mildew, Erysiphe pisi ( Ep ), was observed. LTPG1 was localized to papillae at the sites of Bgh penetration. This study shows that, in addition to the previously known functions, LTPGs contribute to pre‐invasive defence against certain non‐host powdery mildew pathogens.